METHODOLOGICAL TRENDS IN CHEMISTRY TEACHING RESEARCH IN THE JOURNAL “QUÍMICA NOVA NA ESCOLA”-1995 TO 2017 - Bedin, Flávia Caroline; da Silva Costa, Franciellen Rodrigues; Júnior, Alvaro Lorencini; Kiouranis, Neide Maria Michellan [UNESP] (Revista Pesquisa Qualitativa - RPQ, 2020)
With the growth of Teaching of Chemistry as an area of knowledge, it is also growing the diffusion of the research works carried out in this area. Once this field has been consolidated, it is important to understand what methodological trends have been employed. Therefore, we sought to investigate the publications of the section Research in Teaching of Chemistry/ Chemistry in Focus of the journal Química Nova na Escola (QNEsc). After the analysis, we observe that the research has been characterized as to the qualitative character, with the predominance of the case study. We believe that even advancing on the methodological issues, there are still gaps that need to be filled for research to be strengthened and gain more and more significant space in the scientific scenario.
TENDÊNCIAS METODOLÓGICAS DA PESQUISA EM ENSINO DE QUÍMICA NA REVISTA “QUÍMICA NOVA NA ESCOLA”-1995 A 2017
Keywords: Chemical Education; Methodological Trends; QNEsc